Effect of coupling agent on structure and properties of micro–nano composite fibers based on PET. Issue 34 (11th May 2016) - Jiang, Zhaohui; Ma, Pibo; Guo, Zengge; Jia, Zhao; Pu, Congcong; Xiao, Changfa
ABSTRACT: Poly(ethylene terephthalate) (PET)/carbon black (CB) micro–nano composite fibers were manufactured by melt spinning method. To achieve good dispersion, nano‐CB particles were modified by coupling agent (CA). The effect of CA on structure and properties of the fibers were investigated via scanning electron microscopy (SEM), tensile testing, differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD), sonic orientation, and birefringence, respectively. At 2 wt % CA dosage, CB particles present the optimal dispersion in the fibers, shown in SEM images. Besides, the fibers possess the maximum breaking strength, the lowest crystallization temperature, and the highest crystallinity. After CA modification, the superior interfacial structure between PET and CB is beneficial to improve mechanical properties of the fibers. The well dispersed CB particles provide more heterogeneous nucleation points, resulting in the highest crystallinity. Furthermore, the fibers with 2 wt % CA dosage possess the maximum orientation and shrinkage ratio. According to Viogt–Kelvin model, the thermal shrinkage curves of the fibers can be well fitted using single exponential function. The three‐phase structure model of crystal phase–amorphous phase–CB phase was established to interpret the relationship among shrinkage, orientation, and dispersion of CB particles. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43846. Abstract :